Malignant female genital tract smooth muscle tumors with adipocytic differentiation: A morphologic, immunohistochemical, MDM2 fluorescence in situ hybridization and molecular genetic study of 6 lipoleiomyosarcomas - Swanson, Amy A; Michal, Michael; Xing, Deyin; Dashti, Nooshin K; Židlík, Vladimir; Cheek-Norgan, E Heidi; Keeney, Matthew E; Keeney, Gary L; Sukov, William R; Gupta, Sounak; Nucci, Marisa R; Schoolmeester, J Kenneth (Human pathology, 2024)
Leiomyosarcoma with adipocytic differentiation or lipoleiomyosarcoma is an uncommon sarcoma of the female genital tract with only a few individual reports in the literature. We therefore performed a morphologic, immunohistochemical, MDM2 gene amplification and RNA and DNA sequencing analysis of a series of gynecologic lipoleiomyosarcoma to better define the clinicopathologic spectrum. Six tumors from 6 patients were identified and classified as spindled lipoleiomyosarcoma (n = 2), mixed spindled and myxoid lipoleiomyosarcoma (n = 1), epithelioid lipoleiomyosarcoma with focal myxoid features (n = 1) and mixed spindled and epithelioid lipoleiomyosarcoma (n = 2). Patient age ranged from 41 to 64 years (mean: 49; median: 50). Primary location included uterine corpus (3), uterine corpus/cervix (2) and broad ligament (1). Tumor size ranged from 4.5 to 22 cm (mean: 11.2; median: 9.8). Four patients had metastasis at presentation or subsequently developed recurrent or distant disease. Patient status was known for 5: 2 dead of disease, 2 alive with disease and 1 alive without evidence of disease. Immunohistochemical expression of smooth muscle markers, ER, PR and WT-1 showed patterns similar to non-adipocytic gynecologic leiomyosarcomas. MDM2 amplification fluorescence in situ hybridization performed on 2 tumors was negative in 1 and equivocal in 1. Sequencing studies performed on 3 tumors found TP53 mutations in 3, with 1 tumor also having an ATRX alteration. No gene fusions were identified. Although lipoleiomyosarcomas have a diverse morphologic spectrum, our findings suggest the smooth muscle component shares morphologic and immunohistochemical features with female genital tract non-adipocytic leiomyosarcomas. Lipoleiomyosarcomas also have genetic alterations associated with non-adipocytic gynecologic leiomyosarcomas.
Keywords: Molecular Biology; hybridizace in situ fluorescenční; nádor z hladké svalové tkáně; imunohistochemie; Middle Aged; protoonkogenní proteiny c-mdm2; Smooth Muscle Tumor; leiomyosarkom; Adult; Proto-Oncogene Proteins c-mdm2; In Situ Hybridization, Fluorescence; Biomarkers, Tumor; ženské pohlavní orgány; Immunohistochemistry; ženské pohlaví; nádorové biomarkery; Humans; molekulární biologie; Leiomyosarcoma; lidé středního věku; dospělí; Female; lidé; Genitalia, Female